Judicialization of politics, activism and judicial discretion - Cesário, João Humberto (2020)
VERBICARO, Loiane Prado. Judicialização da política, ativismo e discricionariedade judicial. Prefácio de José Eduardo Faria. 2. ed. Rio de Janeiro: Lumen Juris, 2019. 549 p.